INFLUENCES OF GRINDING CONDITIONS ON GALENITE-SPHALERITE FLOTATION KINETICS - Volkan Bozkurt; Işıl Tokcan (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2023)
Grinding is more than just crushing, it is also a process that causes a chemical reaction on the surface of the mineral. Water used in the grinding process significantly affects the galvanic interaction. Different grinding conditions result in different pulp chemistries. This becomes especially important in sulfide flotation in terms of recovery and selectivity. There are limited studies examining the effects of dry and wet grinding prior to the flotation of sulfide minerals. This study compared the effects of wet and dry grinding on the flotation kinetics of complex Pb-Zn sulfide ore at P80 of 20 and 50 µm grind sizes. Results showed that dry grinding positively affected the sphalerite ore flotation compared to wet grinding in terms of recovery and grade in both galenite and sphalerite rougher flotation stages. Considering that the effect of dry grinding was due to the difference in pulp chemistry, the reasons were explored based on particle morphology, and pulp potentials. The results showed that grinding the same ore under dry and wet conditions significantly affected the flotation performance. In light of the pulp potential measurements, it was determined that the reducing environment obtained in the wet grinding negatively affected the flotation performance, while the oxidizing environment formed during the dry grinding affected the flotation performance positively. This was attributed to the fact that galvanic interactions that occurred during wet grinding were significantly reduced during dry grinding. Hence, better galenite and sphalerite flotation was obtained following dry grinding.